Trends in Late-Life Activity Limitations in the United States: An Update From Five National Surveys - Freedman, Vicki A.; Spillman, Brenda C.; Andreski, Patti M.; Cornman, Jennifer C.; Crimmins, Eileen M.; Kramarow, Ellen; Lubitz, James; Martin, Linda G.; Merkin, Sharon S.; Schoeni, Robert F.; Seeman, Teresa E.; Waidmann, Timothy A. (Demography, 2013)
This article updates trends from five national U.S. surveys to determine whether the prevalence of activity limitations among the older population continued to decline in the first decade of the twenty-first century. Findings across studies suggest that personal care and domestic activity limitations may have continued to decline for those ages 85 and older from 2000 to 2008, but generally were flat since 2000 for those ages 65-84. Modest increases were observed for the 55- to 64-year-old group approaching late life, although prevalence remained low for this age group. Inclusion of the institutional population is important for assessing trends among those ages 85 and older in particular.